Do feeding habits influence anthropogenic particle consumption in demersal fish in a tropical estuary? A study from the northern part of the Tropical Eastern Pacific - Green-Ruíz, Carlos René; Amezcua, Felipe; Cruz-García, Roberto; Rivera-Hernández, José R.; Muro-Torres, Víctor M. (Frontiers in Marine Science, 2025)
IntroductionThe presence of anthropogenic particles (AP), defined as materials that have undergone human modification, in an estuarine system, and their consumption by demersal fishes, were assessed in the northern part of the Tropical Eastern Pacific. The aim was to investigate how the type and quantity of microplastics ingested by demersal fish of different trophic levels, feeding habits, and feeding guilds vary, and if these relate to the APs found in water.MethodsWater and fish samples were collected from a network of stations through the estuarine system of Huizache-Caimanero. The presence and characteristics of microplastics were analyzed using Fourier Transform Infrared (FTIR) spectroscopy. A total of 1,162 AP particles were identified in the water samples, with fragments being the most common form. Stomach contents from 133 fish, representing six species across different trophic levels and feeding habits, were examined. These species included planktivores, carnivores, and omnivores, as well as zoobenthivores, piscivores, planktivores, and detritivores.ResultsThe study found a high frequency of microplastic ingestion among fish, with fibers being the most prevalent form. The most common polymers identified in both water and fish were cotton and polyethylene terephthalate (PET). Other polymers detected included alkyd resins in water and nylon in fish, while polyethylene and acrylic were less abundant. These findings align with the types of human activities conducted in the study area.DiscussionOur findings suggest that the position in the water column influences microplastic ingestion, rather than trophic position or feeding habits. This study provides valuable insights into the impact of AP contamination on coastal ecosystems and highlights the need for effective management strategies to mitigate its effects. Future research should focus on the long-term ecological impacts of microplastics and the development of sustainable solutions to address this growing environmental challenge.